A new perspective of modified partition coefficient - Suleman, A. (Pattern Recognition Letters, 2015)
We begin by showing that the modified partition coefficient (MPC) is an average Euclidean distance between membership degrees and the centre of the fuzzy c-partition. Subsequently, we construct alternative MPCs using several other measures of dissimilarity and examine how differently they perform when compared with the original proposal. Empirical evidence shows that the MPC based on a Chernoff's measure of divergence is more robust to the initial conditions of the fuzzy c-means algorithm.